Function and Sexual Satisfaction of Women Treated with Two Types of Ovulation Stimulant Drugs: Clomiphene and Letrozole - Razieh Shams Mourkani; Fariba Fahami; Elham Naghshineh (Mashhad University of Medical Sciences, 2021)
Introduction: Infertility is one of the factors which have a significant effect on the sexual performance of couples, especially women. Infertility can affect sexual activity in infertile couples. On the other hand, ovulation stimulation therapies for infertility treatment can inhibit estrogen and thus reduce women's sexual function and satisfaction. Therefore, this study was performed with aim to determine and compare the sexual performance and satisfaction of women treated with two types of ovulation stimulant drugs: clomiphene and letrozole. Methods: This two-group analytical study was performed on 80 infertile women referred to infertility centers in Isfahan province in 2019. The research tools were the questionnaires of Beck, sexual function and sexual satisfaction, which were completed twice before and after receiving clomiphene and letrozole. Data were analyzed by SPSS software (version 22) and Independent t-test, Mann-Whitney, Chi-square, Paired t-test, Wilcoxon and Friedman tests. P<0.05 was considered statistically significant. Results: In intra-group comparison, there was no statistically significant difference before and after drug administration in the variables of sexual satisfaction (p=0.053) and sexual function (p=0.057), but in inter-group comparison, there was a statistically significant difference in sexual function of the clomiphene group (P <0.001); lower sexual function was reported after clomiphene use than before its use, but in terms of sexual satisfaction in the clomiphene group, no significant difference was reported before and after receiving the drug (p>0.05). There was no significant difference in letrozole group before and after drug administration in both variables of sexual function and satisfaction (p=0.053). Conclusion: The score of sexual performance decreased in the clomiphene group, but sexual satisfaction did not show any difference in any of the groups. In other words, women's sexual function is affected by many factors, one of which is the use of assisted reproductive drugs, including clomiphene. Clomiphene inhibits vaginal moisture by inhibiting estrogen, which can cause pain and reduce sexual arousal, orgasm, and libido in women. For this purpose, it is recommended that active people in the field of infertility pay attention to this issue.